Weight Loss in Cancer Patients Correlates With p38β MAPK Activation in Skeletal Muscle - Zhang, Guohua; Anderson, Lindsey J.; Gao, Song; Sin, Thomas K.; Zhang, Zicheng; Wu, Hongyu; Jafri, Syed H.; Graf, Solomon A.; Wu, Peter C.; Dash, Atreya; Garcia, Jose M.; Li, Yi-Ping (Frontiers in Cell and Developmental Biology, 2021)
Unintentional weight loss, a first clinical sign of muscle wasting, is a major threat to cancer survival without a defined etiology. We previously identified in mice that p38 MAPK mediates cancer-induced muscle wasting by stimulating protein catabolism. However, whether this mechanism is relevant to humans is unknown. In this study, we recruited men with cancer and weight loss (CWL) or weight stable (CWS), and non-cancer controls (NCC), who were consented to rectus abdominis (RA) biopsy and blood sampling (n = 20/group). In the RA of both CWS and CWL, levels of activated p38 MAPK and its effectors in the catabolic pathways were higher than in NCC, with progressively higher active p38 MAPK detected in CWL. Remarkably, levels of active p38 MAPK correlated with weight loss. Plasma analysis for factors that activate p38 MAPK revealed higher levels in some cytokines as well as Hsp70 and Hsp90 in CWS and/or CWL. Thus, p38 MAPK appears a biomarker of weight loss in cancer patients.